Preparation of nanofiltration hollow fiber membrane for acetic acid removal from synthetic hydrolysate - Nurlin Fatin, Mohd Tahirun (2014)
Nanofiltration has a pore size range of 0.001-0.01um. NF membranes can filter particles up to and including some salts, synthetic dies and sugars, however it is unable to remove most aqueous salts and metallic ions, as such, NF is generally confined to specialist uses. Nanofiltration (NF) is a promising membrane separation technology due to its low energy consumption and unique separation properties. The main objective of this research is to produce, characterize and evaluate performance of PES NF hollow fiber membrane for acetic acid removal from biomass hydrolyzate solution. An asymmetric PES hollow fiber membrane was fabricated using a dry/wet spinning process with forced convection in the dry gap. The PES concentration be fix at 20wt%, but the value of additive (PVP) is increase from 1wt% and 9wt.% and the rest is the value for NMP which act as solvent. The membranes were then analyzed by using scanning electron microscope (SEM) and high performance liquid chromatography (HPLC). Increase the concentration of PVP resulting decreased the rejection of the component it will increase the number of pore at the membrane and resulting in permeability of the membrane which increase of concentration of PVP will increase the permeability of the membrane. The increasing of additive concentration tends to increase the salt permeability while reducing the effective membranes thickness. In this case, the thickness of the effective membrane layer (dense layer) is very important and well known as one of the determining factors influencing the membranes separation ability